Exotic noble gas carbene-like ions (2014)
ABSTRACT: Using a combination of theoretical techniques, this work studies the Kr2C2+ species, which has electronic, structural, and some typical chemical characteristics of carbenes, and whose ground state is singlet. Similarly to the case of traditional carbenes, Kr2C2+ is metastable and appears to be a candidate for a reactive intermediate.